Death at the manor - Schellman, Katharine (Schellman, Katharine. Lily Adler mystery, 2022)
"Regency widow Lily Adler is looking forward to spending the autumn away from the social whirl of London. When she arrives in Hampshire with her friends, the Carroways, she doesn't expect much more than a quiet country visit and the chance to spend time with her charming new acquaintance, Matthew Spencer. But something odd is afoot in the small country village. A ghost has taken up residence in the Belleford manor, a lady in grey who wanders the halls at night, weeping and wailing. Half the servants have left in terror, but the family seems delighted with the notoriety that their ghost provides. Intrigued by this spectral guest, Lily and her party immediately make plans to visit Belleford. They arrive at the manor the next morning ready to be entertained--only to find that tragedy has struck. The matriarch of the family has just been found killed in her bed. The dead woman's family is convinced that the ghost is responsible. Lily is determined to learn the truth before another victim turns up--but could she be next in line for the Great Beyond?"--Dust jacket flap.